Animal performance in oat and Italian ryegrass pastures under leaf lamina biomass levels - Bandinelli, Duilio Guerra (2005)
The objective of this work was to evaluate the effect of different leaf lamina biomass over animal performance. A mixture of oat (Avena strigosa Schreb) and Italian ryegrass (Lolium multiflorum Lam.) was used to determine adequate levels of leaf lamina biomass for pasture management. Two trials were made, in 2002 and 2003 cool seasons. In 2002 evaluation, leaf lamina biomass values were of 360 kg ha-1 (low) and 630 kg ha-1 (high). In 2003, values obtained for leaf lamina biomasses were of 352, 422 and 507 kg ha-1, being classified as low, medium and high, respectively. Grazing method was continuous, with variable stocking rate; testing animals were calves of Charolais breed and its crosses with Nelore breed, with initial age of nine months. Evaluated variables in animal production, in both years, were: average daily gain, stocking rate and live weight gain per area. Leaf lamina biomasses evaluated are not limiting factors to animal performance.